2021
DOI: 10.1109/jsac.2021.3088715
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Low-Altitude Air-to-Ground Spatial Channel Characterization for Cellular Networks Connectivity

Abstract: Cellular-connected unmanned aerial vehicles (UAVs) have recently attracted a surge of interest in both academia and industry. Understanding the air-to-ground (A2G) propagation channels is essential to enable reliable and/or highthroughput communications for UAVs and protect the ground user equipments (UEs). In this contribution, a recently conducted measurement campaign for the A2G channels is introduced. A uniform circular array (UCA) with 16 antenna elements was employed to collect the downlink signals of tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Citation information: DOI 10.1109/TAP.2020.3016164, IEEE Transactions on Antennas and Propagation for the takeoff-and landing scenario, which considers heights between 30 m and 330 m. Link distance ranges from 500 m to 350 km. Based on a extensive measurement campaign using an UAV and a commercial LTE BS in suburban environments, the publications [24], [55], [56] were released. In [24], [55] a stochastic channel model was proposed, including characterizations of path loss, shadow fading, delay spread and Doppler frequency spread for horizontal and vertical flights at different heights and distances to the BS.…”
Section: A Related Workmentioning
confidence: 99%
“…Citation information: DOI 10.1109/TAP.2020.3016164, IEEE Transactions on Antennas and Propagation for the takeoff-and landing scenario, which considers heights between 30 m and 330 m. Link distance ranges from 500 m to 350 km. Based on a extensive measurement campaign using an UAV and a commercial LTE BS in suburban environments, the publications [24], [55], [56] were released. In [24], [55] a stochastic channel model was proposed, including characterizations of path loss, shadow fading, delay spread and Doppler frequency spread for horizontal and vertical flights at different heights and distances to the BS.…”
Section: A Related Workmentioning
confidence: 99%
“…Many measurement-based investigations such as [21]- [25] have demonstrated that the A2G propagation channels at higher heights are nearly LoS. For example, 3GPP [21] suggests a LoS probability of 1 for rural area and moderately high UAV altitude larger than 40 m, which is also verified by the measurements in [25] for even lower heights. In [22], path loss exponents (PLEs) were found to be almost free-space values as 2.1 and 2 at 60 m and 120 m, respectively.…”
Section: A Low Altitude A2g Propagation Channelsmentioning
confidence: 72%
“…In [23], [24], the Rician K-factors of the A2G channels were found to be large for most cases at higher heights with mean value around 15 dB. Although in few cases, the K-factor could be smaller due to, e.g., the reflections from buildings [24], [25] in urban or industrial areas, spatial analysis in [25] for the A2G channels has shown that the additional cluster(s) are usually separable to the LoS cluster in the azimuth domain with angle differences larger than 60 • . This means that if a UAV is equipped with directional antennas, even the channel with several clusters can probably be simplified as a single-cluster channel with a high K-factor.…”
Section: A Low Altitude A2g Propagation Channelsmentioning
confidence: 95%
“…Based on a extensive measurement campaign using an UAV and a commercial LTE BS in suburban environments, the publications [24], [55], [56] were released. In [24], [55] a stochastic channel model was proposed, including characterizations of path loss, shadow fading, delay spread and Doppler frequency spread for horizontal and vertical flights at different heights and distances to the BS.…”
Section: A Related Workmentioning
confidence: 99%